Flaviviruses induce ER-specific remodelling of protein synthesis. - Ho Him Wong; Dorian Richard Kenneth Crudgington; Lewis Siu; Sumana Sanyal (PLoS Pathogens)
Flaviviruses orchestrate a unique remodelling of the endoplasmic reticulum (ER) to facilitate translation and processing of their polyprotein, giving rise to virus replication compartments. While the signal recognition particle (SRP)-dependent pathway is the canonical route for ER-targeting of nascent cellular membrane proteins, it is unknown whether flaviviruses rely on this mechanism. Here we show that Zika virus bypasses the SRP receptor via extensive interactions between the viral non-structural proteins and the host translational machinery. Remarkably, Zika virus appears to maintain ER-localised translation via NS3-SRP54 interaction instead, unlike other viruses such as influenza. Viral proteins engage SRP54 and the translocon, selectively enriching for factors supporting membrane expansion and lipid metabolism while excluding RNA binding and antiviral stress granule proteins. Our findings reveal a sophisticated viral strategy to rewire host protein synthesis pathways and create a replication-favourable subcellular niche, providing insights into viral adaptation.